Media Informasi untuk Perawatan Kucing berbasis Android - Rasyid Hardi Wirasasmita; Muhamamad Zamroni Uska; Jamaluddin Jamaluddin; GB Deni Rahman (Jurnal Pendidikan Informatika (EDUMATIC), 2023)
The use of information technology so far is not only in the field of education, but can also be utilized in the health sector, such as cat care. Raising a cat has different needs and ways of caring for other animals such as feeding, drinking, shelter, and health. This study aims to produce android-based cat care information media, knowing the feasibility and response of users. This type of research is research and development using the Rapid Application Development (RAD) model which consists of 3 stages, namely: requirements planning, RAD design workshop, and implementation. The subjects in this study amounted to 19 cat owners to find out the user's response. Data collection techniques using questionnaires and data analysis using quantitative descriptive. Our findings show that the application developed is in the form of Android-based cat care information media. The material expert due diligence result is 96.3% (very feasible). Meanwhile, the results of the due diligence of media experts obtained 87% (very feasible). Thus this application is worthy of being used as an android-based cat care information media. So that this application can help some parties or cat owners to take care of their cats without having to go to a veterinary clinic.